Fundamentação teórica e prática para o processo de indicação geográfica das atividades físicas em meio à natureza - Messias, Sérgio Murilo Carvalho (2016)
Leisure activities, physical and sports activities carried out in the middle of the nature are increasingly practiced and they are subject to strong normatization and regulation of organs controllers. Considering its great importance in the economic scenario and in its different modalities, these practices, comes if highlighting increasingly through its potential labor income generation and employment. Ensure that a physical and sporting activity is performed with safety in the environment or in environmental preservation areas is an important factor for the public organs, both by the issue of the preservation of the environment, as the safety of involved. The following certification rules established at international guides published by International Standards Organization, and consists in the declaration that a product, process, system or person is in accordance with the requirements specified in the technical standards. These standards of certification currently are directed to support Ecotourism and Adventure Tourism and do not meet the specificities of a Physical Activity be performed in the middle of the nature. The objective of this study is to seek theoretical and practical for the certification of paths through the nature by Geographical Indication, enabling an effective control of physiological and psychological relations of practitioners of such arrangements. In this study are also addressed the key issues relating to the set of existing certifications and systems that meet certain specific features, but which will serve as a reference for a theoretical underpinning for the possible creation of a certification program of course by the geographical indication in Brazil, because the geographical indications may be considered a type of certification belonging to the area of intellectual property and more specifically of industrial property.